Solve the factored quadratic equation (19x−3)(x−9)=0

(
19
𝑥

3
)
(
𝑥

9
)
=
0
.(1 point)
Responses

The solution set is x={−9, −319}
𝑥
=
{

9
,


3
19
}
.
The solution set is x={−9, −319}
𝑥
=
{

9
,


3
19
}
.

The solution set is x={3, 9}
𝑥
=
{
3
,

9
}
.
The solution set is x={3, 9}
𝑥
=
{
3
,

9
}
.

The solution set is x={319, 9}
𝑥
=
{
3
19
,

9
}
.
The solution set is x={319, 9}
𝑥
=
{
3
19
,

9
}
.

The solution set is x={193, 9}
𝑥
=
{
19
3
,

9
}
.

11 answers

To solve the factored quadratic equation \((19x−3)(x−9)=0\), we can set each factor equal to zero.

  1. Set the first factor to zero: \[ 19x - 3 = 0 \] \[ 19x = 3 \] \[ x = \frac{3}{19} \]

  2. Set the second factor to zero: \[ x - 9 = 0 \] \[ x = 9 \]

So, the solutions to the equation are: \[ x = \frac{3}{19} \quad \text{and} \quad x = 9 \]

Thus, the solution set is: \[ x = \left{ \frac{3}{19}, 9 \right} \]

Based on the response options provided, the correct solution set is: The solution set is \( x = \left{ \frac{3}{19}, 9 \right} \) (though there may not be a perfectly matching option).

Solve the quadratic equation 84x2+16x=0

by factoring out the GCF.(1 point)
Responses

The solutions are x=−421

The solutions are x=0 and x=421

The solutions are x=−4 and x=−421

The solutions are x=0 and x=4

To solve the quadratic equation \(84x^2 + 16x = 0\) by factoring out the greatest common factor (GCF), we first identify the GCF of the terms.

The GCF of \(84x^2\) and \(16x\) is \(4x\).

Now, we can factor the equation:

\[ 84x^2 + 16x = 4x(21x + 4) = 0 \]

Next, we'll set each factor equal to zero:

  1. From the factor \(4x = 0\): \[ x = 0 \]

  2. From the factor \(21x + 4 = 0\): \[ 21x = -4 \] \[ x = -\frac{4}{21} \]

Thus, the solutions to the equation \(84x^2 + 16x = 0\) are: \[ x = 0 \quad \text{and} \quad x = -\frac{4}{21} \]

Given the response options provided, the correct solution set is: The solutions are \(x = 0\) and \(x = -\frac{4}{21}\) (though this option doesn't appear exactly in your list). If \( -\frac{4}{21} \) is meant to resemble the format for one of the other options, you might clarify or check them again, as they do not match the calculated solutions.

Find the mistake made when solving x2−96=4x
x2−96=4x

Step 1: x2+4x−96=0
Add 4x to both sides.
Step 2: (x+12)(x−8)=0

Factor.
Step 3: x+12=0 or x−8=0
Use the Zero Product Property.
x=−12 or x=8

Responses:

Step 2 - She did not factor correctly.

Step 1 - She added 4x to both sides instead of subtracting.
Step 1 - She added 4 x to both sides instead of subtracting.

She did not make any mistakes.

Step 1 - She did not set it =0, so she did not use the Zero Product Property correctly.

Let's analyze the provided steps for solving the equation \( x^2 - 96 = 4x \).

Step 1: Rearranging the Equation

The original equation is: \[ x^2 - 96 = 4x \] The first step involves moving all terms to one side: \[ x^2 - 4x - 96 = 0 \] In this step, instead of adding \(4x\) to both sides, it should have been subtracted from both sides to set the equation to zero correctly.

Step 2: Factoring

The equation \(x^2 - 4x - 96 = 0\) can be factored as: \[ (x + 12)(x - 8) = 0 \] This step is correctly factored.

Step 3: Zero Product Property

Using the Zero Product Property correctly gives two potential solutions: \[ x + 12 = 0 \quad \Rightarrow \quad x = -12 \] \[ x - 8 = 0 \quad \Rightarrow \quad x = 8 \]

Conclusion

The mistake in the solution occurs in Step 1, where it was incorrectly stated that \(4x\) was added to both sides instead of subtracted to bring it to the left side. Thus, the correct response is:

Step 1 - She added \(4x\) to both sides instead of subtracting.

Solve the following quadratic equation using the perfect square trinomial pattern:

x2+x+0.25=0 0.25
Responses

x=0.25

x=0.5

x=−0.25

x=−0.5

To solve the quadratic equation \(x^2 + x + 0.25 = 0\) using the perfect square trinomial pattern, we'll follow these steps:

  1. Recognize the perfect square trinomial: The equation can be rewritten as: \[ x^2 + x + \left(\frac{1}{2}\right)^2 = 0 \] Here, \(\left(\frac{1}{2}\right)^2 = 0.25\).

  2. Rewrite the equation as a perfect square: \[ (x + 0.5)^2 = 0 \]

  3. Take the square root of both sides: \[ x + 0.5 = 0 \]

  4. Solve for \(x\): \[ x = -0.5 \]

Thus, the solution to the equation \(x^2 + x + 0.25 = 0\) is: \[ \boxed{x = -0.5} \]

Based on the provided responses, the correct solution is: \(x = -0.5\).

Ginger was asked to solve 25x2−196=0 by factoring using the difference of squares pattern. What is/are the correct solution(s)?
Responses

x=196/25

x=14/5

x=−14/5, x=14/5

To solve the equation \(25x^2 - 196 = 0\) by factoring using the difference of squares pattern, we can follow these steps:

  1. Recognize the difference of squares: The equation \(25x^2 - 196\) can be expressed as a difference of squares: \[ (5x)^2 - (14)^2 = 0 \]

  2. Apply the difference of squares formula: The difference of squares can be factored as: \[ (5x - 14)(5x + 14) = 0 \]

  3. Set each factor to zero: We set each factor equal to zero: \[ 5x - 14 = 0 \quad \text{or} \quad 5x + 14 = 0 \]

    • For \(5x - 14 = 0\): \[ 5x = 14 \quad \Rightarrow \quad x = \frac{14}{5} \]

    • For \(5x + 14 = 0\): \[ 5x = -14 \quad \Rightarrow \quad x = -\frac{14}{5} \]

  4. Write the solutions: The solutions are: \[ x = \frac{14}{5} \quad \text{and} \quad x = -\frac{14}{5} \]

Based on the response options provided, the correct solution is: \(x = -\frac{14}{5}, x = \frac{14}{5}\).

Complete the square to solve the following quadratic equation: x2−6x−20=20

Responses

x=10, x=−4

x=−10, x=4

x=52, x=−46

To solve the quadratic equation \(x^2 - 6x - 20 = 20\) by completing the square, follow these steps:

  1. Simplify the equation: Start by moving \(20\) to the left side: \[ x^2 - 6x - 20 - 20 = 0 \] \[ x^2 - 6x - 40 = 0 \]

  2. Isolate the quadratic and linear terms: Add \(40\) to both sides: \[ x^2 - 6x = 40 \]

  3. Complete the square: To complete the square, take half of the coefficient of \(x\) (which is \(-6\)), square it, and add it to both sides. Half of \(-6\) is \(-3\), and squaring it gives \(9\).

    Add \(9\) to both sides: \[ x^2 - 6x + 9 = 40 + 9 \] \[ (x - 3)^2 = 49 \]

  4. Take the square root of both sides: \[ x - 3 = \pm 7 \]

  5. Solve for \(x\):

    • For \(x - 3 = 7\): \[ x = 10 \]
    • For \(x - 3 = -7\): \[ x = -4 \]

Thus, the solutions to the equation \(x^2 - 6x - 20 = 20\) are: \[ x = 10, \quad x = -4 \]

Based on the response options provided, the correct solution is: \(x = 10, x = -4\).